PERENCANAAN, IMPLEMENTASI, DAN TANTANGAN PENGEMBANGAN KETERAMPILAN SOSIAL SISWA SD MELALUI MODEL PEMBELAJARAN KOOPERATIF (STUDI LITERATUR) - Agustina Yulianti; Taufik Muhtarom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the planning, implementation, and challenges of developing elementary school students' social skills through the cooperative learning model. This research method uses a literature study method by reviewing 30 relevant journal articles published between 2020-2026. The data collection technique is through the Google Scholar database using specific keywords. The process of selecting articles goes through the stages of inclusion and exclusion. Including (1) the researcher entered the keyword "Social Skills", resulting in 145,000 articles; (2) the researcher added the keyword "Elementary School Students", resulting in 9,670 articles; (3) the researcher further added the keyword "Cooperative Learning", resulting in 2,490 articles; (4) the researcher filtered the articles based on the publication year, resulting in 1,930 articles; (5) the researcher filtered the articles by applying the include and exclude process, resulting in 112 articles; and (6) the researcher downloaded the articles that were accessible and had title relevance, totalling 30 articles. Data analysis was conducted in four stages: (1) source collection, namely the identification and downloading of 30 relevant articles through a systematic procedure; (2) source criticism, namely checking the truth and authenticity of the obtained sources; (3) interpretation, namely interpreting the obtained facts to clearly understand their meaning; (4) historiography, namely compiling the entire series of obtained facts into a systematic written form. The research results indicate that the planning for the development of social skills is carried out through the preparation of Learning Implementation Plans (RPP) or teaching modules, the creation of a learning environment that supports collaboration, the selection of appropriate cooperative learning types, and the design of learning activities that encourage active student involvement. Implementation is carried out through the stages of cooperative learning, namely the delivery of learning objectives, the formation of heterogeneous groups, discussion activities, presentations, evaluations, and the awarding of rewards. Various types of cooperative learning, such as STAD, Jigsaw, Think Pair Share (TPS), Team Games Tournament (TGT), Make a Match, Cooperative Integrated Reading and Composition (CIRC), Snowball Throwing, and Course Review Horay, combined with learning media such as mind mapping, video shows, comics, and Quizziz, can enhance students' abilities to cooperate, communicate, interact, empathise, take responsibility, tolerate, actively participate, and manage themselves. The challenges encountered include differences in students' character and abilities, imbalanced participation within groups, limited learning time, and teachers' competence in managing group dynamics. Thus, the cooperative learning model is an effective approach in developing the social skills of elementary school students if supported by thorough planning, systematic implementation, and optimal classroom management.